QUALITY OF ELECTRONIC POPULATION CARD SERVICES AT THE MALEBER DISTRICT OFFICE, KUNINGAN DISTRICT - Pudjiaraka, Pandu (Journal of Economic Development and Village Building, 2024)
Sport tourism is a potential that can be developed by every area, because sport and tourism can support each other which in turn can trigger a good economic impact on the area. The sport of running which is very popular recently has resulted in many running events in every city. This sport has become a lifestyle in several cities, including Yogyakarta. Jogja is one of the areas where sports events (running) are often held. This sporting lifestyle has many potential economic impacts on the surrounding area, such as coffee shops which are usually a gathering point for the running community. According to previous research, after a sporting event each region will receive an impact such as the regional economy will develop, therefore the researcher wants to know whether there is an economic impact on the UMKM (Coffee Shop) and how this happens will be analyzed qualitatively by the researcher.